POLA DAN JARINGAN PROSTITUSI TERSELUBUNG DI KOTA PADANG - Erianjoni, Erianjoni; Ikhwan, Ikhwan (Humanus, 2012)
As the world's oldest social problems prostitution has always existed anddeveloped along along with the structural changes in the society. In the city of Padangprostitution is conducted underground with various forms and patterns within socialnetworks. This study reveals patterns formed and social networks used by prostitutes oractors in the business. This qualitative study uses purposive sampling to selectinformants. Data is collected by limited participation observation, interviews, anddocumentary study. The study found that prostitution in Padang city has particularstrategy to gain customers as well as avoid law enforcement raids.Kata kunci : underground prostitution, prostitution patterns, social networks